Effects of therapeutic and toxic doses of levamisole on thyroid hormones and some biochemical parameters in sheep - Atessahin, A; Karahan, I; Pirincci, I (Wiley, 2004)
This study was carried out to establish the effects of therapeutic and toxic doses of levamisole on thyroid hormone levels and some biochemical parameters in sheep. Twelve Akkaraman ewes were used. Levamisole was given orally at doses of 7.5 mg kg(-1) (group 1) and 40 mg kg(-1) (group 2) to the animals. Blood samples were taken from the jugular vein at 2, 4, 8, 24, 48, 96 and 144 h after the administrations. Serum thyroid hormones and some biochemical parameters were determined on these samples. When compared with the control levels, no significant changes were observed in triiodothyronine (T3) and thyroxin (T4) levels in group 1. Although levamisole was found to increase the levels of total T3, it decreased the levels of total T4 in group 2. On the other hand, free T3 and free T4 levels were not changed in either group. While serum alkaline phosphatase (ALP) activities were decreased, aspartate aminotransferase (AST), alanine aminotransferase (ALT), lactate dehydrogenase (LDH) and creatinine kinase (CK) activities were increased significantly by levamisole. However, it increased the serum albumin and cholesterol levels, but decreased the inorganic phosphate levels in groups 1 and 2. On the other hand, when compared with the control levels, no significant changes were detected in serum sodium, potassium and calcium levels. In conclusion, therapeutic and toxic doses of levamisole were determined to affect thyroid metabolism and some biochemical parameters in sheep. Copyright (C) 2004 John Wiley Sons, Ltd.
Keywords: levamisole; sheep; thyroid hormones; biochemical parameters